Guidelines for cold‐regions groundwater numerical modeling. (8th July 2020) - Lamontagne‐Hallé, Pierrick; McKenzie, Jeffrey M.; Kurylyk, Barret L.; Molson, John; Lyon, Laura N.
Abstract: The impacts of ongoing climate warming on cold‐regions hydrogeology and groundwater resources have created a need to develop groundwater models adapted to these environments. Although permafrost is considered relatively impermeable to groundwater flow, permafrost thaw may result in potential increases in surface water infiltration, groundwater recharge, and hydrogeologic connectivity that can impact northern water resources. To account for these feedbacks, groundwater models that include the dynamic effects of freezing and thawing on ground properties and thermal regimes have been recently developed. However, these models are more complex than traditional hydrogeology numerical models due to the inclusion of nonlinear freeze–thaw processes and complex thermal boundary conditions. As such, their use to date has been limited to a small community of modeling experts. This article aims to provide guidelines and tips on cold‐regions groundwater modeling for those with previous modeling experience. This article is categorized under: Engineering Water > Methods Science of Water > Hydrological Processes Abstract : Model development steps for a cryohydrogeologic numerical model. T is temperature, P is pressure, sat. is saturation, BCs stands for boundary conditions, Δ t is the time step size, and Δ x and Δ y and the model mesh discretization lengths.